Use of fuzzy logic to optimize fertilizer application on brizantha grass - Godinho, Emmanuel Zullo [UNESP]; Caneppele, Fernando de Lima; Gasparotto, Helio Vagner [UNESP] (Univ Tecnologica Fed Parana-utfpr, 2022)
Brachiaria is considered essential for bovine feeding. Therefore, the producer seeks to find the best fertilizer dosages for high yields. The general objective of this work was to present a model, based on indicators and fuzzy logic, to optimize the dosages of two fertilizers in a Brachiaria cultivar. Variables related to fertilizers (mineral and organic) and to the height of the plant (in cm) were used to enter this system. The best results after optimizing the entry rules for the application of mineral and organic fertilizers were between 0 to 20 and 150 to 200 with 130 to 150 and 180 to 200, respectively in g/m(2), respectively. With the application of fuzzy rules using real data, it can present great benefits to those involved in the livestock production chain, thus being able to reduce the dosages in the applications and improving its final profitability.
Keywords: Sustainability; Brachiaria brizantha; Fuzzy Logic Application